Relationship between anomalous Ettingshausen effect and anomalous Nernst effect in an FePt thin film. (30th May 2018) - Seki, T; Iguchi, R; Takanashi, K; Uchida, K
Abstract: We investigated anomalous Ettingshausen effect (AEE) and anomalous Nernst effect (ANE) for the same device consisting of an FePt thin film. The temperature modulation due to the AEE was visualized using the active infrared emission microscopy, called lock-in thermography. On the other hand, the ANE voltage was detected under the temperature gradient induced by the heater built into the device. We experimentally evaluated the magnitudes of AEE and ANE, taking into account the heat loss to the substrate, and discussed the relationship between AEE and ANE.